Proteomic Analysis of MeJa-Induced Defense Responses in Rice against Wounding - Bertini, Laura (Int J Mol Sci, 2019)
The role of jasmonates in defense priming has been widely recognized. Priming is a physiological process by which a plant exposed to low doses of biotic or abiotic elicitors activates faster and/or stronger defense responses when subsequently challenged by a stress. In this work, we investigated the impact of MeJA-induced defense responses to mechanical wounding in rice (Oryza sativa). The proteome reprogramming of plants treated with MeJA, wounding or MeJA+wounding has been in-depth analyzed by using a combination of high throughput profiling techniques and bioinformatics tools. Gene Ontology analysis identified protein classes as defense/immunity proteins, hydrolases and oxidoreductases differentially enriched by the three treatments, although with different amplitude. Remarkably, proteins involved in photosynthesis or oxidative stress were significantly affected upon wounding in MeJA-primed plants. Although these identified proteins had been previously shown to play a role in defense responses, our study revealed that they are specifically associated with MeJA-priming. Additionally, we also showed that at the phenotypic level MeJA protects plants from oxidative stress and photosynthetic damage induced by wounding. Taken together, our results add novel insight into the molecular actors and physiological mechanisms orchestrated by MeJA in enhancing rice plants defenses after wounding.